2018
DOI: 10.19173/irrodl.v19i2.3479
|View full text |Cite
|
Sign up to set email alerts
|

Connecting OER With Mandatory Textbooks in an EFL Classroom: A Language Theory–Based Material Adoption

Abstract: Systemic functional linguistics (SFL) theory focuses on developing language learners' meta-linguistic understanding of the interrelation among linguistic form (grammar/vocabulary), meaning, and context. Guided by SFL when using a mandatory textbook and open educational resources, this study investigates how exposure to this blended teaching and learning context may impact English-as-aforeign-language (EFL) learners' adjustment to materials used in their learning, as well as their learning practices. By drawing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 25 publications
2
37
0
1
Order By: Relevance
“…In the field of language teaching, Gebhard, Chen, Graham, and Gunawan's (2013) SFL-based education of pre-service and in-service English teachers who were enrolled in a Master's program in the United States illustrated that these teachers (including those from an EFL context) were able to understand writing and reading as a meaning-making process and demonstrate interactions between meaning and linguistic resources in their own texts (e.g., projecting objective tone through nominalization or inanimate subjects). Despite the power of SFL in assisting language teachers' development as shown in these studies, limited research has highlighted the challenges of teaching/learning SFL in the language classroom (Zhang, 2018), with the relevant previous studies focusing on teachers' academic performance following training (e.g., Huang et al, 2017). In addition, there is almost no such research in the field of distance teacher education for teachers in constrained contexts.…”
Section: Sfl-based Distance Educationmentioning
confidence: 99%
“…In the field of language teaching, Gebhard, Chen, Graham, and Gunawan's (2013) SFL-based education of pre-service and in-service English teachers who were enrolled in a Master's program in the United States illustrated that these teachers (including those from an EFL context) were able to understand writing and reading as a meaning-making process and demonstrate interactions between meaning and linguistic resources in their own texts (e.g., projecting objective tone through nominalization or inanimate subjects). Despite the power of SFL in assisting language teachers' development as shown in these studies, limited research has highlighted the challenges of teaching/learning SFL in the language classroom (Zhang, 2018), with the relevant previous studies focusing on teachers' academic performance following training (e.g., Huang et al, 2017). In addition, there is almost no such research in the field of distance teacher education for teachers in constrained contexts.…”
Section: Sfl-based Distance Educationmentioning
confidence: 99%
“…Many studies have documented the importance of materials in the language learning classroom in both ESL and EFL contexts (e.g., Tomlinson, 2012;Zhang, 2018). Namely, they are the resources students and teachers depend on to deliver and accumulate knowledge, respectively.…”
Section: E-learning Resources As Learning Materialsmentioning
confidence: 99%
“…For example, in Yang et al's (2013) research, which focused on a semesterlong general education course in a university in Taiwan, their quantitative research demonstrated that through an online platform as well as teacher mediation, students became able to actively invest themselves in analyzing or evaluating listening or speaking content. Regarding this issue, researchers have called for attention to be paid to the pedagogical design of online resources and to focus more on the way of using and implementing online resources as learning materials in the classroom (Taffs & Holt, 2013;Zhang, 2018). Given the integrated relationship between language and meaning embedded in writing, it seems worthwhile to explore the use of online resources as learning materials to impart the interplay between language and meaning and engage students in critically understanding and composing writing.…”
Section: E-learning Resources As Learning Materialsmentioning
confidence: 99%
“…The word count for each argumentative writing was approximately 1,000 -1,500 words. During his self-development, in addition to the reading content in the mandatory textbook, Henry's teaching was primarily conducted in accordance with the SFL-based construct, while corresponding online materials were selected and used for class or assigned to students for their after-class practice (see Table 1 below; see also Zhang, 2018). The overall purpose of the self-directed curriculum was primarily concerned with using SFL-informed online resources to help students understand the knowledge related to the mystery of writing.…”
Section: Research Context: Curriculum and Classroom Settingmentioning
confidence: 99%
“…In response to the constraining factors mentioned above that affect effective college writing instruction, teachers' self-directed development (i.e. reliance on themselves) in optimizing available resources is useful to better prepare students for successful writing (Zhang, 2018). In particular, given that textbooks teachers rely on to develop students' writing knowledge generally include writing structure guidelines, sample writing, and unprincipled knowledge (Zhang, 2017), supplementing classroom writing instruction with other resources is suggested; for example, using online resources because of their convenience and wide availability (Kwak, 2017;Yuan & Recker, 2015).…”
Section: Introductionmentioning
confidence: 99%